Erratum: Profile and Appropriateness of Antibiotic Use Among Outpatients with Respiratory Tract Infections at the Pagantenan Subdistrict Community Health Center - Zakaria Zakaria; Lisa Narulita; Sufiyatin Riski Adawiyyah; Akhmad Fathir (Universitas Muhammadiyah Sidoarjo, 2027)
This erratum provides corrections to the author information of the article “Profile and Appropriateness of Antibiotic Use Among Outpatients with Respiratory Tract Infections at the Pagantenan Subdistrict Community Health Center,” originally published in Academia Open, Vol. 11 No. 2 (2026), DOI: 10.21070/acopen.11.2026.14738. The correction includes presenting Zakaria as the author name, adding Sufiyatin Riski Adawiyyah to the author list, correcting the spelling of Akhmad Fathir’s name, and completing the authors’ professional credentials, affiliation, and email addresses. These corrections are intended to ensure accurate author attribution and appropriate metadata for citation and indexing. No changes are made to the scientific content, data, results, discussion, or conclusions of the original article. The corrected author information should be used in the article metadata and subsequent citation and indexing records. The original article is available at https://doi.org/10.21070/acopen.11.2026.14738.